Searchlight on the Duchess of Atholl - Atholl, Katharine Marjory Stewart-Murray, Duchess of, 1874-1960. Searchlight on Spain.; Maitland, Frank (Edinburgh : Revolutionary Socialist Party, 1938)
1938 SA01-17-013 16 pages 15B/8/71